2021
DOI: 10.9734/jpri/2021/v33i59a34334
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Parents Regarding DKA Symptoms in their Children with Type I DM

Abstract: Background: Diabetic ketoacidosis (DKA) is a common emergency and life-threatening illness. Also, if not detected early, early treatment in the emergency room can cause serious complications. The goal of managing type 1 diabetes is to maintain the correct levels of blood sugar, glycated hemoglobin (HbA1c), blood pressure, lipid levels, and body weight while avoiding hypoglycemia. Treatment of type 1 diabetes requires proper insulin treatment, proper nutrition, physical activity, preventive education, and patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
0
2
Order By: Relevance
“…Younger female patients who were unmarried and currently studying were more associated with having better awareness levels, but the differences in the awareness levels between the more educated subjects and less educated ones did not reach statistical significance (P = 0:057). In a study conducted in India [10,14], they found a significant relationship between educational status and the knowledge about DKA while in Abha, Saudi Arabia [12,13,15,16], low knowledge levels were more common among lesseducated parents, being a father aged more than 40 years, unemployed or those nonhealthcare parents, and having a lower monthly income which contradicted our reports. Furthermore, we observed that patients who have been diagnosed with type 1 DM with associated DKA were seen to have an increased level of awareness.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Younger female patients who were unmarried and currently studying were more associated with having better awareness levels, but the differences in the awareness levels between the more educated subjects and less educated ones did not reach statistical significance (P = 0:057). In a study conducted in India [10,14], they found a significant relationship between educational status and the knowledge about DKA while in Abha, Saudi Arabia [12,13,15,16], low knowledge levels were more common among lesseducated parents, being a father aged more than 40 years, unemployed or those nonhealthcare parents, and having a lower monthly income which contradicted our reports. Furthermore, we observed that patients who have been diagnosed with type 1 DM with associated DKA were seen to have an increased level of awareness.…”
Section: Discussioncontrasting
confidence: 97%
“…According to their accounts, insufficient awareness was detected among patients regarding the risk factors, complications, and management of DKA while in India [9,10], and most diabetic patients (80%) appeared to have a poor level of DKA knowledge. However, in a study published in Somalia [11][12][13], the knowledge, attitude, and practice of the patients who visited Egyptian Hospital in Mogadishu, Somalia, regarding diabetic complications were satisfactory which was better than our reports. The current gap in awareness may not only sustain a significant burden with the cost of treatment on the patients and their families but it may also lead to severe complications that can be lifethreatening if not diagnosed and treated early.…”
Section: Discussioncontrasting
confidence: 83%
“…Also, participants who think that diabetic patient has high knowledge about DKA are significantly associated with low levels of awareness. Although, these results could be different from other studies, like the study from Hamed et al (2021) [14]. These differences could be attributed to different samples, times and socioeconomic status.…”
Section: Discussioncontrasting
confidence: 80%